SENSE OF HUMOR AND LOVE OF LIFE AS PREDICTORS OF ADJUSTMENT IN YOUNG ADULTS - Prof. Uzma Jabeen; Faiza Zafar; Prof. Mehlaqa Riaz (International Journal of Contemporary Issues in Social Sciences, 2024)
The present study was carried out to explore the relationship between sense of humor, love of life and adjustment in young adults. A convenient sampling strategy was used to approach 200 young adults (n=100 men, n=100 women). Sense of Humor Questionnaire-6 (Sven Svebak,1996), Love of Life Scale (Ahmed Abdel-Khalek, 2007) and Brief Adjustment Scale (Cruz et al., 2019) were used in the study. Reliability analysis was done for all the measures. Pearson product moment correlation (r) was carried out to find out the relationship between sense of humor, love of life and adjustment in young adults. Findings indicated a significant positive relationship between sense of humor and love of life. Independent sample t-test was employed to analyze the gender differences. Results indicated that women reported higher levels of sense of humor as compared to men. Similarly, men reported having strong love of life and better adjustment levels as compared to women. Multiple linear regression was run to find out the predictive power of sense of humor and love of life against adjustment. Findings revealed love of life as statistically significant positive predictor of adjustment while sense of humor did not significantly predict adjustment.